Eksperimen Pembuatan Ice Gel Skala Rumah Tangga Sebagai Media Pendingin Cool Box Untuk Ikan Hasil Tangkap atau Pasca Panen - Ully Wulandari; Beta Indi Sulistyowati; Suharyanto; Kadi Istrianto; Dian Sutono HS (Sam Ratulangi University, 2023)
The majority of fishermen in the coastal areas of Karawang are traditional fishermen with small boats. The condition of a small boat certainly does not allow for cool storage in the ship's hatch, so that bulk ice cubes are a way out for fishermen to maintain the quality of the fresh quality of the fish they catch so that the selling price does not fall. This research was conducted in the coastal area of Karawang from July-December 2022. The study was conducted by trials of making ice gel with the addition of alcohol and salt. The manufacture of ice gel is carried out on a household scale with ingredients that are easy to obtain and affordable. The results of making ice gel are tested for durability with the following results: Ice gel with added salt has a fast freezing time when compared to ice gel with additional alcohol, ice gel with added salt can maintain cold (freezing) temperatures better than ice gel with additional alcohol. The test results of fish samples stored using ice gel with the addition of salt have less ALT value than ice gel with the addition of alcohol, meaning that bacteria do not develop much in fish stored with salt ice gel so that the quality of fish freshness is maintained properly.